2011
DOI: 10.1074/jbc.m110.184648
|View full text |Cite
|
Sign up to set email alerts
|

ThnY Is a Ferredoxin Reductase-like Iron-Sulfur Flavoprotein That Has Evolved to Function as a Regulator of Tetralin Biodegradation Gene Expression

Abstract: Previous genetic studies in Sphingomonas macrogolitabida strain TFA have established that expression of genes involved in tetralin biodegradation (thn genes) requires the function of the LysR type activator ThnR and also ThnY. Sequence comparison indicated that ThnY is homologous to bacterial oxygenase-coupled NAD(P)H-dependent ferredoxin reductases. However, ThnY showed substitutions in highly conserved positions of the pyridine nucleotide binding domain of these ferredoxin reductases. ThnY expression is co-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…MexS is a member of the MDR2 family (medium-chain dehy- (12). Interestingly, ThnY and ThnR are also purported to transduce metabolic redox signals emerging from the tetralin catabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MexS is a member of the MDR2 family (medium-chain dehy- (12). Interestingly, ThnY and ThnR are also purported to transduce metabolic redox signals emerging from the tetralin catabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The natural substitution of this conserved Cys residue observed in MhpP is rare in FNR and FNR-like proteins. However, natural loss of the highly conserved Cys of yXCGp was reported for an iron-sulfur flavoprotein involved in tetralin biodegradation (García et al 2011). Substrate specificity analyses confirmed that MhpP preferentially utilizes NADPH rather that NADH as an electron donor (Table 3).…”
Section: Discussionmentioning
confidence: 62%
“…In case of aromatic degradation, they are not only part of the ring hydroxylating dioxygenases, but also participate in peripheral pathways. ThnY from Sphingomonas macrogolitabida strain TFA is a ferredoxin reductase-like protein but has a regulatory function in tetralin degradation instead of a catalytic one [24]. Aldo-keto reductases have trans-dihydrodiol dehydrogenase activity which results in the formation of quinones from polyaromatic hydrocarbons and ultimately form catechol and ROS [3].…”
Section: Discussionmentioning
confidence: 99%